2016
DOI: 10.1097/md.0000000000005271
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine bathing for the prevention of colonization and infection with multidrug-resistant microorganisms in a hematopoietic stem cell transplantation unit over a 9-year period

Abstract: Health care associated infections (HAIs) are currently among the major challenges to the care of hematopoietic stem cell transplantation (HSCT) patients. The objective of the present study was to evaluate the impact of 2% chlorhexidine (CHG) bathing on the incidence of colonization and infection with vancomycin-resistant Enterococcus (VRE), multidrug-resistant (MDR) gram-negative pathogens, and to evaluate their CHG minimum inhibitory concentration (MIC) after the intervention.A quasi-experimental study with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 35 publications
1
15
2
9
Order By: Relevance
“… 14 Mendes et al also found that Vancomycin Resistant Enterococcus (VRE) colonization and infection rates fell when CH soaps were used for bathing, but the Gram-negative infection rate was not affected. 15 Moreover, Petlin et al found that the rate of infection with methicillin-resistant Staphylococcus aureus fell upon bathing with CH soap. 16 We found that the CHG dressing prevented Gram-positive CRBSIs.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Mendes et al also found that Vancomycin Resistant Enterococcus (VRE) colonization and infection rates fell when CH soaps were used for bathing, but the Gram-negative infection rate was not affected. 15 Moreover, Petlin et al found that the rate of infection with methicillin-resistant Staphylococcus aureus fell upon bathing with CH soap. 16 We found that the CHG dressing prevented Gram-positive CRBSIs.…”
Section: Discussionmentioning
confidence: 99%
“…However, this impact has not been reproduced in other studies . Interestingly, in a recent report, the use of a chlorhexidine wash was associated with an increased risk of infections caused by MDR‐GNB, including carbapenem‐resistant Enterobacteriaceae, as well as the development of reduced susceptibility to chlorhexidine and the presence of efflux‐mediated resistance genes in staphylococci …”
Section: Preventing Infectionmentioning
confidence: 94%
“…Some practices, such as antiseptic whole‐body washing or bathing of patients, have been shown by some researchers to reduce VRE and MRSA colonization and infections in hematologic units and have been proposed by some for selected patients with recurrent MRSA soft tissue infections . However, this impact has not been reproduced in other studies .…”
Section: Preventing Infectionmentioning
confidence: 99%
“…[32]. Eine signifikante Reduktion von VRE-Kolonisationen und -Infektionen durch Chlorhexidin-Waschungen konnte auch bei einer 9 Jahre dauernden Studie auf einer Stammzelltransplantationseinheit in Brasilien gezeigt werden [33]. Allerdings ergaben sich auch deutlich negative Nebeneffekte in Form von erhöhter MHK (minimale Hemmkonzentration) gegenüber Chlorhexidin, einer Häufung gramnegativer Infektionen sowie eines Ausbruchs mit multiresistentem P. aeruginosa.…”
Section: Intensivierung Der Reinigungsleistungunclassified